The future of the ASEAN Regional Forum (ARF) - Desker, Barry (2022)
Security analysts generally compare the elaborate structures for maintaining regional order in the North Atlantic with the rudimentary processes in the Asia Pacific. In contrast to the North Atlantic Treaty Organization (NATO) and the Organization for Security and Co-operation in Europe (OSCE), the ASEAN Regional Forum (ARF) serves primarily as a process for facilitating security dialogues and engaging in confidence-building measures in the Asia-Pacific region. Since its inception in 1994, the ARF has been led by the ASEAN states which have used the ARF process to engage the major powers. However, it is increasingly recognised even within ASEAN that fundamental changes are necessary if the ARF is to become the primary vehicle for inter-governmental security cooperation in the Asia Pacific region.